2008
DOI: 10.1002/asna.200811069
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of tidal tails

Abstract: We examine the longitudinal distribution of the stars escaping from a cluster along tidal tails. Using both theory and simulations, we show that, even in the case of a star cluster in a circular galactic orbit, when the tide is steady, the distribution exhibits maxima at a distance of many tidal radii from the cluster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…On the one hand, streams intrinsically host variations in their densities, as shown by early numerical experiments by Combes et al (1999). Küpper et al (2008) explained that the motions of stars along streams lead to orbital crowding at the epicycles (i.e. a slowing down of the stars at a fixed position, see also Capuzzo Dolcetta et al 2005).…”
Section: Stellar Streamsmentioning
confidence: 99%
“…On the one hand, streams intrinsically host variations in their densities, as shown by early numerical experiments by Combes et al (1999). Küpper et al (2008) explained that the motions of stars along streams lead to orbital crowding at the epicycles (i.e. a slowing down of the stars at a fixed position, see also Capuzzo Dolcetta et al 2005).…”
Section: Stellar Streamsmentioning
confidence: 99%
“…The data show a linear trend which almost follow same slope. For the nbody6 results as shown in Fig.2 (6) which shows the speed of evolution for a GC only due to two body relaxation mechanism in lack of existence of external tidal field. However a GC without exposure to external tidal field evolves and loses some of its stars due to two-body relaxation mechanism, but N-body simulations [16] have shown that for isolated clusters this process is inefficient in dissolving star clusters since even low-mass clusters would need more than whole life time of the universe to completely evaporate and dissolve.…”
Section: Simulation Results and Disscusionmentioning
confidence: 92%
“…On the observational side, the evidence for differences in the stellar mass-functions of globular clusters [1,2], which are believed to be at least partly the result of their dynamical evolution, and the discovery of extratidal stars surrounding globular clusters so-called tidal tails [3,4] are strong indications for the ongoing dynamical evolution and dissolution of globular clusters. The tidal tails of globular clusters have been simulated and virtualized by some authors [5][6][7]. According to the relatively low distance among the stars in globular clusters and also definition of the relaxation time, they are classified as collisional systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that when stars escape from star clusters through the Lagrangian points form complicated structures known as tidal tails or tidal arms (e.g., [17,38,61,67,68]).…”
Section: Formation Of Spiral Armsmentioning
confidence: 99%